Changing landscape of liver cirrhosis in multi-racial Asian country: a decade comparison - Nik Muhamad Affendi, Nik Arsyad; Sekaran, Sharini; Azmi, Siti Sholihah; Mohd Mahyudin, Nazlin Adlina; Rajaram, Ruveena Bhavani; Mahadeva, Sanjiv (Springer, 2022)
Objectives: Viral hepatitis B was a commonest cause of cirrhosis in Asian countries, however with the rising prevalence of obesity and prevention strategy for viral hepatitis B, we predict that there is a change in the epidemiology of cirrhosis. Our aim is to determine the change of aetiology of cirrhosis and hepatocellular carcinoma in our centre. Materials and Methods: A cross sectional study was conducted where we recruited all cirrhosis patients who were attending inpatient and outpatient service in our centre from July 2019 to July 2021. Baseline demography and clinical characteristics were collected via electronic medical record system. Data collected was analyzed and compared with historical data from our centre that was collected approximately a decade ago, from April 2006 to May 2009. Results: A total of 354 patients were recruited into this study con- sisting of 198 male (55.9%) and 156 female (44.1%) with mean age of 63.36 year-old (20–90). The aetiologies of cirrhosis were NASH, n = 144, (40.7%); viral hepatitis B, n = 78, (22%); viral hepatitis C, n = 31, (8.8%); alcohol, n = 29, (8.2%); hepatitis B ? NASH, n = 16, (4.5%); cryptogenic, n = 23, (6.5%) and autoimmune hep- atitis, n = 11, (3.1%). NASH was the leading aetiology among Malays (50.4%) compared to Indians (46.3%) and Chinese (32%). Hepatitis B was the main aetiology among Chinese (33.3%) compared to Malays (16%) and Indians (6.3%). Alcohol was the predominant aetiology among Indians (25%) compared to Chinese (4.8%) and Malays (0%). 48 patients (13.6%) had HCC with viral hepatitis B being the dominant cause (45.8%) followed by NASH (18.8%) and alcohol (6.3%). Conclusion: Our study showed that there was a drastic change in epidemiology of cirrhosis where the predominant aetiology have changed from viral hepatitis B to NASH. However, viral hepatitis B remained the commonest cause of HCC followed by NASH.